Urgensi Pengelolaan Pembiayaan dalam Upaya Meningkatkan Kualitas Pendidikan di Madrasah - Hendra Naldi; Hadiyanto Hadiyanto (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This research aims to improve the education qualities in Madrasah (Islamic school) by managing the funding. The background of the study indicates the readiness of madrasah to improve the quality of education through madrasah-based management which seems questionable. Some factors indicating the weakness of the quality of education in madrasah are the problem of the financing management system. Madrasah requires the management of financing because it generally develops and is managed independently. In order to improve the quality of education, madrasah should meet the minimum financing management criteria. The intended financing consists of investment, operating, and personal costs. There are three things the madrasah must do in financing management, including planning, implementing, evaluating and accountability.